The mediating effect of work environment on the relationship between organizational citizenship behaviour and job performance: A study of nurses in government hospitals in Kedah - Othman, Noraini; Ali, Hassan (Universiti Utara Malaysia, 2007)
Organizational citizenship behaviour (OCB) refers to a general set of behaviours exhibited by employees that are helpful, discretionary, and go beyond normal job requirements.OCB also improve organizational efficiency and effectiveness by contributing to resource transformations, innovativeness, and adaptability.This research investigates the relationship between OCB and job performance among staff nurses in government hospitals in Kedah.Further, the study will also examine the mediating effect of work environment on the OCB-job performance relationship.A number of 580 staff nurses from a total of 1759 staff nurses, and a total of 70 superiors (sisters) of nine government hospitals involved in this study.Measures of OCB and job performance were obtained from two ratings, which are, superior-ratings and self-ratings.The findings of the study indicated that self-ratings of OCB were significantly higher than superior-ratings of OCB.On the other hand, results revealed that superior-ratings of job performance were significantly higher than self-ratings. Staff nurses also were found to have positive feeling towards their workplace and felt that their participation in the hospitals is good.When both self-ratings of OCB and job performance were used in the analysis, 11% of the variance in job performance was accounted for by OCB.Altruism, courtesy, conscientiousness, and civic virtue were significantly related to job performance.When both superior-ratings of OCB and job performance were used in the analysis, 26% of the variance in job performance was accounted for by OCB.Altruism, courtesy, conscientiousness, and sportsmanship were significantly related to job performance.Further, the results indicated that work environment has partial mediation effect on the relationship between OCB and job performance when both self-ratings of OCB and job performance were used in the analysis. Furthermore, about 12.3% of the total effect of OCB on job performance was mediated by work environment.